From Tradition to Industrialization: A Historical Study on the Transformation of Indonesia’s Jamu Industry - Irwan Hidayat; Wahyu Widayani; Tsabit Azinar Ahmad; Eka Yudha Wibowo; Nanda Julian Utama (istory Department, Faculty of Social Sciences, Universitas Negeri Semarang in collaboration with Masyarakat Sejarawan Indonesia (Indonesian Historical Society), 2025)
Abstract: Indonesia’s exceptional biocultural richness has long sustained jamu, a plant-based healing tradition that blends empirical practice with cosmological notions of bodily balance, yet in the twentieth century jamu businesses shifted from household decoctions and itinerant vendors into branded, standardized consumer health products; this article traces that transformation through a historical case study of Tolak Angin (Sido Muncul), arguing that the transition was propelled by commodification of family recipes in the early 1900s, state recognition and regulation that framed jamu as “Indonesia’s original medicine” during the post-independence decades, and late-twentieth-century modernization in technology and marketing that introduced ready-to-drink sachets, GMP/CPOTB compliance, and clinical evidence supporting OHT status while repositioning jamu as hygienic, practical, and urban-friendly; using qualitative historical reconstruction from archival and printed sources with rigorous source criticism and chronological–thematic narration, the study shows how industrialization preserved and re-signified jamu into a hybrid good—simultaneously heritage and modern therapy—delivering market expansion without severing cultural meaning; the findings imply that policy can strategically couple standards, R&D, biodiversity stewardship, and cultural branding to grow domestic and export markets and to uplift producer communities; the article’s novelty lies in its historically grounded synthesis linking technological standardization, state policy, and cultural consumption to explain how a legacy remedy operationalizes Indonesia’s health-heritage economy. Abstrak: Keanekaragaman hayati-budaya Indonesia sejak lama menopang jamu sebagai tradisi penyembuhan nabati yang memadukan praktik empiris dengan gagasan keseimbangan tubuh-alam, namun pada abad ke-20 bisnis jamu bertransformasi dari godokan rumahan dan penjual gendong menjadi produk kesehatan bermerek dan terstandar; artikel ini menelusuri perubahan tersebut melalui studi kasus historis Tolak Angin (Sido Muncul), menunjukkan bahwa peralihan didorong oleh komodifikasi resep keluarga pada awal 1900-an, pengakuan serta regulasi negara yang memosisikan jamu sebagai “Obat Asli Indonesia” pada era pascakemerdekaan, dan modernisasi teknologi-pemasaran akhir abad ke-20 yang menghadirkan sachet siap minum, kepatuhan GMP/CPOTB, serta bukti klinis menuju OHT sembari mereposisikan jamu sebagai higienis, praktis, dan selaras gaya hidup urban; melalui rekonstruksi sejarah kualitatif berbasis arsip dan literatur dengan kritik sumber dan penulisan kronologis-tematis, studi ini memperlihatkan bagaimana industrialisasi melestarikan sekaligus memaknai ulang jamu menjadi komoditas hibrida—warisan budaya sekaligus terapi modern—yang memperluas pasar tanpa memutus makna budaya; implikasinya, kebijakan perlu mengintegrasikan standar mutu, litbang, pelestarian biodiversitas, dan branding budaya untuk memperkuat pasar domestik maupun ekspor serta memberdayakan komunitas produsen; kebaruan artikel terletak pada sintesis historis yang mengaitkan standardisasi teknologi, kebijakan negara, dan konsumsi budaya guna menjelaskan operasionalisasi ekonomi warisan kesehatan Indonesia.